Intraventricular hemorrhage in preterm newborn: Predictors of mortality - Piccolo, Benedetta; Marchignoli, Mariacristina; Pisani, Francesco (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Intraventricular haemorrhage (IVH) is a cause of morbidity and mortality in preterm infants. It occurs primarily in preterm newborns with an incidence of about 20% and, despite the evolution of neonatal care that allows more and better survival, continues to be a cause of morbidity and mortality in all intensive care units. Our research aimed to evaluate the independent risk factors of mortality and the relative odds ratio for each degree of IVH.Methods: In this retrospective study were included 96 preterm infants, born between 23^ and 36^ weeks of gestational age, which developed IVH of degree two-three-four diagnosed by means of cranial ultrasound. It was made a comparison within the sample by distinguishing the group with IVH degree two from degrees three and four.Results: IVH of degree three and four was independently associated with mortality. We found a higher number of deaths in the GAs